Variabilitas Kontribusi Sistem Energi dalam Bola Basket di Berbagai Posisi Bermain, Fase Permainan, dan Tingkat Kompetisi: Tinjauan Sistematis - Saddan Pramana Putra; M. Furqon Hidayatullah; Slamet Riyadi; Hanik Liskustyawati; Ardyansyah Arief Budi Utomo (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. Basketball performance involves intermittent high-intensity activity requiring continuous interaction between anaerobic and aerobic energy systems. Although numerous studies have examined metabolic demands in basketball, findings remain fragmented when analyzed separately by playing position, phase of play, or competition level. This systematic review aimed to synthesize existing evidence on how energy system contributions vary across these three contextual dimensions. Materials and Methods. A systematic review was conducted in accordance with the PRISMA 2020 guidelines. Literature searches were performed in PubMed, Scopus, SPORTDiscus, and Google Scholar for studies published between 2015 and 2025. Following title abstract screening and full-text evaluation, 15 studies met the inclusion criteria and were included in a qualitative synthesis. A meta-analysis was not performed due to substantial heterogeneity in study designs, outcome measures, and methodological approaches across the included studies. Results. The included studies predominantly investigated elite male basketball players, with fewer studies examining youth athletes and female players. Across studies, consistent patterns of energy system utilization were identified. Guards demonstrated the greatest reliance on ATP-PC and glycolytic systems due to frequent accelerations, changes of direction, and short-duration peak efforts. Forwards exhibited a mixed anaerobic–aerobic metabolic profile reflecting multifunctional tactical roles, whereas centers predominantly relied on the ATP-PC system associated with repeated jumping, physical contact, and explosive actions. Across game phases, fast-break and transition play were dominated by ATP-PC contribution, while prolonged half-court play showed increased glycolytic involvement. Conclusion. Energy system contributions in basketball vary systematically according to playing position, phase of play, and competition level. However, interpretation of these findings is limited by methodological heterogeneity and the indirect estimation of energy system contributions. Despite these limitations, the integrated synthesis provides a comprehensive framework to inform position-specific and context-sensitive conditioning strategies.